Pengaruh Masa Inkubasi Biakan Trichoderma sp Terhadap Kerapatan Spora Dan Viabilitasnya - Ni Nyoman Ana Andari; Moh. Yunus; Asrul Asrul (Mitra Sains, 2020)
Trichoderma sp is one of the biological control agents for controlling pests and diseases of plants. This research aims at identifying the effect of incubation period of the multiply Trichoderma sp to the density of spores and it’s viability produced by each incubation period of Trichoderma sp cultures that were tested. The research was conducted in Laboratory of UPT Proteksi Tanaman Perkebunan on Dinas Perkebunan dan Peternakan Provinsi Sulawesi Tengah, from June to October 2017. Observation variable covers: spores and viability of Trichoderma sp. The result of this research shows that the incubation period of the multiply Trichoderma sp 7 days produces the highest density of spores 8.12 x 108 and viability spores 100%. Thus the spore density and viability of Trichoderma sp in this research classified as good.